The Effect of Product Variation, Brand Image and Price Perception on Purchase Decisions of Fried Sedaap Noodles at Smbako Agent in Kumpay Village, Banten - Ilma Fitria; Resti Hardini; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine the effect of product variations, brand image, and price perceptions on purchasing decisions for fried noodles at basic food agents in the Kumpay sub-district, Banten. The sample in this study were 100 respondents who had purchased fried noodles at least once. This study uses primary data with data collection methods through questionnaires distributed to 100 respondents. The data analysis technique uses inferential analysis with multiple linear regression and uses the Statistical Product and Service Solution (SPSS) version 22.0 program. From the results of multiple linear regression analysis, using the t test where Product Variation (X1) has a positive and significant effect on purchasing decisions with a score of 3.665 > 1.985. Brand Image (X2) has no positive and significant effect on purchasing decisions with a score of 1.276 <1.985 and Price Perception (X3) has a positive and significant effect on purchasing decisions with a score of 4.873 > 1.984. So it can be concluded that Product Variation and Perceived Price have a positive effect on purchasing decisions. Meanwhile, brand image has no positive and significant effect on purchasing decisions.